ANALISIS SEMIOTIKA DALAM KUMPULAN CERPEN PELANGI DI UJUNG SENJA KARYA RATIH AYUNINGRUM - Sri Juniati; Andi Muhammad Yahya (STKIP Paris Barantai, 2021)
The aims of this research are To describe semiotics in the collection of short stories Pelangi di Ujung Senja by Ratih Ayuningrum. Describe the dominance of semiotics in the collection of short stories Pelangi di Ujung Senja by Ratih Ayuningrum. The method used is a descriptive qualitative research method that describes semiotics in the collection of short stories Pelangi di Ujung Senja by Ratih Ayungingrum. Researchers as a key instrument. The collection of short stories Pelangi di Ujung Senja by Ratih Ayungrum as primary data and secondary data are books related to semiotic theory, literary theories, research methods and other books as supporting research. The results of the research on the collection of short stories Pelangi di Ujung Senja by Ratih Ayuningrum, showed that Semiotics in the collection of short stories Pelangi di Ujung Senja contained four, namely index, sign, icon and gesture. While the type of semiotics that dominates in the collection of short stories Pelangi di Ujung Senja by Ratih Ayuningrum is the index type, with a total of 44 citations. Kata Kunci: Semiotika, Cerpen.